IMPLEMENTASI MODEL PEMBELAJARAN SENTRA DALAM MENANAMKAN NILAI MORAL AGAMA ANAK USIA DINI DI TK SITTI MASYITHAH PALU - Endang Hasrina (Musawa: Journal for Gender Studies, 2024)
The purpose of this study is to find out the planning of the center learning model in instilling religious moral values in Sitti Masyithah Palu Kindergarten, to know the implementation of the center learning model in instilling religious moral values in Sitti Masyithah Palu Kindergarten and to find out the implications of the center learning model in instilling early childhood religious moral values in Sitti Masyithah Palu Kindergarten. This research is a descriptive research with a qualitative approach. The subjects of this study are coordinators, educators and parents. Data collection was carried out using observation, interview, and documentation methods. The researcher is the main instrument in conducting research assisted by observation guidelines, interview guidelines, and documentation guidelines. The techniques used in data analysis are data display, data reduction, and conclusion making. The results of the study show that: 1) Planning of the Center Learning Model at Sitti Masyithah Kindergarten Palu is by using several methods, namely: play method, habituation method, story method, tourism work method, exemplary method, demonstration method, question and answer method. 2) The implementation of the center learning model in instilling early childhood religious moral values in Sitti Masyithah Palu Kindergarten includes planning, implementation and evaluation. Planning in it includes the preparation of Syllabus, RPT, RPB, RPM and SKH. The implementation has several stages of activities including opening activities, core activities and closing activities. From some of these activities, it can be seen that there is a level of achievement in the development of aqidah, akhlaq and worship. Evaluation includes observation, anecdotal recording, conversations, assignments, performances and works. 3) The implications of the center learning model in instilling religious moral values in early childhood at Sitti Masyithah Palu Kindergarten show good implications, where children can speak honestly, politely, politely, and speak good words.